Afrikaanse plaas versus Antilliaanse plantage. Ruimte, lokaliteit en identiteit in "Mijn zuster de negerin" van Cola Debrot - Koch, Jerzy (Tydskrif vir Letterkunde Society, University of Pretoria, 2006)
African farm versus Antillean plantation. Propositions formulated with reference to one literary tradition could have a stimulating effect on research conducted in another. This contribution is aimed at establishing whether it is possible to analyse Dutch Antillean literature with Afrikaans literary concepts. To illustrate this, Cola Debrot’s (1902-1981) "Mijn zuster de negerin" (My sister, the Negress, 1935) will be placed within the framework of the Afrikaans plaasroman (farm novel). This historical subgenre of the South African novel came to full bloom in the 1930s and 1940s. Central to the plaasroman is the farm-experience. The fact that contemporary Afrikaans authors are still interested in this novelistic mode testifies to its viability, which derives from the ample scope it provides for giving expression to problems concerning identity and locality. "Mijn zuster de negerin", a true classic of Dutch literature, is studied here through the prism of the most typical elements of the plaasroman, for example the close connection with the soil and with nature, the space of the rural districts, the 'plaas' as an idyllic place, the motif of the prodigal son, the rejection and acceptance of an inheritance/a legacy, the motif of the ancestors and rebellion against the older generation or the patriarchal order. Special emphasis is placed on the motif of house/homestead and barnyard, as the experience of these spaces contains the quintessence of all the other important motifs. Since the issue of identity and locality is central also to Debrot’s novella, the Afrikaans plaasroman provides an expansive framework within which this Dutch story can be interpreted.
Afrykańska farma versus antyliańska plantacja. Przestrzeń, lokalność i tożsamość w "Mojej siostrze Murzynce" Coli Debrota
Keywords: Afrikaans literature; Dutch literature; farm novel; plaasroman; Cola Debrot; Dutch Antillean literature; identity; locality; space